Arachnoid cyst as a complication of ventriculoperitoneal shunt: Case illustration - Kaplan, Metin; Erol, Fatih Serhat; Gerçek, Ebru; Orhan, Haci (Turkish Neurosurgical Society, 2006)
Development of an arachnoid cyst after ventriculo-peritoneal shunting is extremely rare. The authors present an unusual cause of arachnoid cyst formation following surgery performed for cystic dilatation of the 4th ventricle. Cyst to peritoneal shunting was.performed and the patient developed a supratentorial arachnoid cyst 8 months later.
Keywords: Arachnoid cyst; Complications of shunts; Hydrocephalus